2002
DOI: 10.1034/j.1399-302x.2002.170310.x
|View full text |Cite
|
Sign up to set email alerts
|

An essential amino acid residue for catalytic activity of the dextranase of Streptococcus mutans

Abstract: Dextranase (Dex) is an enzyme that hydrolyzes glucan, a polymer of glucose synthesized from sucrose by glucosyltransferases (GTFs). By comparing amino acid sequences of Dexs and GTFs, we found that the Dex enzymes of Streptococcus mutans, Streptococcus sobrinus, Streptococcus downei and Streptococcus salivarius had similar amino acid sequences to those of the catalytic sites of GTFs of mutans streptococci. We therefore examined the amino acid essential in Dex catalysis by molecular genetic approaches in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…This is consistent with the report that the mutation of S. mutans dextranase at the Asp-385, corresponding to residue 453 of S. criceti dextranase (Fig. 5B), abrogated the dextranase activity (14). As Asp-453 was shown to be critical for dextranase activity in S. criceti, this residue has been considered part of a catalytic site of dextranase.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is consistent with the report that the mutation of S. mutans dextranase at the Asp-385, corresponding to residue 453 of S. criceti dextranase (Fig. 5B), abrogated the dextranase activity (14). As Asp-453 was shown to be critical for dextranase activity in S. criceti, this residue has been considered part of a catalytic site of dextranase.…”
Section: Discussionsupporting
confidence: 81%
“…6A and B, lane 2). This observation was consistent with the demonstration that a mutation of the Asp-385 residue of S. mutans dextranase resulted in the disappearance of the dextranase activity (14). A single codon TGG codes for a single amino acid tryptophan (Trp).…”
Section: Determination Of the Dextranase Activity Of Dextranase Mutansupporting
confidence: 75%
See 2 more Smart Citations
“…An SDS-PAGE analysis of the recombinant enzyme indicated that there are multiple active dextranase forms (77). Comparison of the amino acid sequences of the Dex proteins and glucosyltransferases indicated that the amino acid sequences of the Dex enzymes produced by S. mutans, S. sobrinus, S. salivarius, and S. downei were similar to those of the catalytic sites of glucosyltransferases of mutans streptococci (78,137).…”
Section: Sequence Comparison Studiesmentioning
confidence: 94%